Diction and Social Status in Sasak Language - Istikhorini Atika (IJECA (International Journal of Education and Curriculum Application), 2018)
This paper aims to discuss varied dictions that emerge towards different social status in Sasak community. By using purposive sampling technique, several Sasak speakers who have diverge social status in community were taken as the sample. Data of this study were gathered through ethnographic observations and interviews, and then analyzed using ethnography of communication and analysis of interaction. The research finding showed the mostly found diction forms of Sasak language are pronominal persona marking. Sasak speakers tend to use high Sasak (base alus) when speaking with someone who has honorific title such as menak or hajj. However, if the relationship is intimate, the Sasak diction will be switched into plain Sasak (Sasak jamaq) even to those having honorific title. The intimate relation among family can break the use of high Sasak (base alus), especially for hajj, but it rarely happens among close friendship. Conversely, the high Sasak (base alus) or vernacular Sasakized Indonesian is used in order to save face in the interactions among stranger.